2000
DOI: 10.1002/etc.5620190805
|View full text |Cite
|
Sign up to set email alerts
|

A study of the structure and metal tolerance of the soil microbial community six years after cessation of sewage sludge applications

Abstract: Abstract-Changes in soil microbial community structure and development of metal tolerance as a result of past applications of unamended sewage sludge and metal-amended sewage sludge were found in soils of a long-term field experiment at Braunschweig, Germany. Both the rate of sewage sludge application and metal amendment affected the size and activity of the microbial biomass and had caused changes in microbial community structure as seen by differences in phospholipid fatty acid (PLFA) profiles. Past sewage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…Given that the majority of changes are seen in the culturable portion of the bacterial community it was not surprising that C-FAME and epi£uorescence counts were not sensitive enough to determine the impact of the contaminants. In previous studies, the e¡ect of heavy metals on soil fatty acid pro¢les was not consistent [27,28] and the results here substantiate that observation.…”
Section: Discussionsupporting
confidence: 67%
“…Given that the majority of changes are seen in the culturable portion of the bacterial community it was not surprising that C-FAME and epi£uorescence counts were not sensitive enough to determine the impact of the contaminants. In previous studies, the e¡ect of heavy metals on soil fatty acid pro¢les was not consistent [27,28] and the results here substantiate that observation.…”
Section: Discussionsupporting
confidence: 67%
“…Adaptation usually results in changes of community composition and the maintenance of soil functionality up to high concentrations of metals in soil Bååth et al 1998;Witter et al 2000). Microbial processes differ in their susceptibility to stresses, with for instance nitrification being more sensitive than soil respiration (Domsch 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors showed that environmental stress e.g. metals or organic contaminants can provoke such changes in community structure and successively cause development of community tolerance Pennanen et al, 1996;Ba˚a˚th et al, 1998a, b;Kelly et al, 1999;Macnaughton et al, 1999;Gong et al, 2000;Witter et al, 2000).…”
Section: Introductionmentioning
confidence: 99%